2014
DOI: 10.3892/mmr.2014.2120
|View full text |Cite
|
Sign up to set email alerts
|

Selective β2 adrenergic agonist increases Cx43 and miR-451 expression via cAMP-Epac

Abstract: Abstract. It has been demonstrated that connexin 43 (Cx43) and microRNAs have significant roles in glioma. Cyclic adenosine monophosphate (cAMP) is suggested to be a regulator of connexins and microRNAs. However, it remains elusive whether cAMP and exchange protein directly activated by cAMP (Epac2), have a regulatory effect on Cx43 and microRNA-451 (miR-451) in astrocytoma cells. We treated 1321N1 astrocytoma cells with a selective β2 adrenergic agonist and a selective Epac activator with and without adenyl c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 26 publications
2
11
0
Order By: Relevance
“…In the present study, significant correlations between Epac1 and PKC immunoreactivity on one hand, and between Epac1 and Cx43 immunoexpression on the other hand, were observed in lung cancer tissues, indicating that Epac1 may be involved in the regulation of lung cancer cell proliferation through the PKC and Cx43 proteins. These findings were consistent with previous reports [28,29].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In the present study, significant correlations between Epac1 and PKC immunoreactivity on one hand, and between Epac1 and Cx43 immunoexpression on the other hand, were observed in lung cancer tissues, indicating that Epac1 may be involved in the regulation of lung cancer cell proliferation through the PKC and Cx43 proteins. These findings were consistent with previous reports [28,29].…”
Section: Discussionsupporting
confidence: 94%
“…It was shown that Epac can induce PKC activation and Cx43 phosphorylation [28]. The complex cAMP-Epac2 increases Cx43 expression, and Epac2 overexpression inhibits glioma cell proliferation [29]. In the present study, significant correlations between Epac1 and PKC immunoreactivity on one hand, and between Epac1 and Cx43 immunoexpression on the other hand, were observed in lung cancer tissues, indicating that Epac1 may be involved in the regulation of lung cancer cell proliferation through the PKC and Cx43 proteins.…”
Section: Discussionsupporting
confidence: 60%
“…In contrast, little is known about Epac2 regulation of miRNAs in the heart. Recent studies indicated that Epac modulated the expression of miRNAs in other cell types, as it is the case of miR-20 in macrophages 27 , and miR-451 in astrocytoma cells 28 .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, susceptible animals also exhibit enhanced cardiac β-AR responsiveness, presenting a dominant functional contribution of the β 2 -adrenergic receptors following MI, both in vivo and in vitro (Billman et al, 1997 ; Houle et al, 2001 ). Notably, acute β 2 -AR stimulation can increase junctional conductance and protein expression in cardiac myocytes (Xia et al, 2009 ), likely via the exchange protein directly activated by cAMP (Epac)/Rap1 signaling pathway (Somekawa et al, 2005 ; Duquesnes et al, 2010 ; Mostafavi et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%